Reductive immobilization of Cr(VI) in contaminated water by tannic acid. (June 2022) - Jiang, Xiaofeng; Long, Wenjun; Peng, Liangqiong; Xu, Teng; He, Faming; Tang, Yuling; Zhang, Wenhua
Abstract: The rapid reductive immobilization of Cr(VI) from the aqueous solution was achieved by reduction to Cr(III) using tannic acid (TA), and subsequent pH-triggering precipitation of the organo-Cr(III) complexes formed in the redox reaction. The effects of TA concentration, temperature, and solution pH on the reduction of Cr(VI) were examined by batch experiments, and the rapid redox reduction followed a second-order kinetics with respect to Cr(VI) concentration in the pH range of 2.0–3.0. UV–visible spectra, FTIR, and XPS confirmed the complete detoxification of Cr(VI) concomitant with carboxylation of partial phenolic hydroxyls in TA. Synchronously, the reduced Cr(III) coordinated with carboxyl groups in oxidized TA (OTA) to form complexes, which exhibited remarkable pH-dependent size distribution characteristics as illustrated by SEM images and sequential filtration/ultrafiltration. The resulted Cr(III) complexes could aggregate into colloids with larger size and precipitate out at pH range of 6.0–8.0 via cross-linking, thereby leading to 93% Cr and 89% TOC immobilization. An eco-friendly and cost-effective method for Cr(VI) elimination and immobilization is provided because polyphenols are natural polymers derived from plants. Graphical abstract: Image 1 Highlights: TA can effectively reduce Cr(VI) under acidic conditions. Reduced Cr(III) coordinated with oxidized TA to form organo-Cr(III) complexes. The Cr(III) complexes exhibit pH-dependent size distribution characteristics. Cr(III) and organics are simultaneously immobilized by co-precipitation.